Dor abdominal crônica em pediatria e consumo excessivo de FODMAPS - relato de caso - Bruna Caseri Marino; Natascha Silva Sandy; Maria Angela Bellomo Brandão (Sociedade Brasileira de Pediatria, 2022)
Abdominal pain affects up to 45% of children aged 4 to 18 years. Functional disorders rank as the main cause. There is no consensus over what constitutes "minimal" investigation for the management of pediatric patients with chronic abdominal pain. This case report presents and discusses a case of long-term chronic abdominal pain involving a child previously submitted to extensive complementary investigation, in which detailed clinical evaluation found the patient was in a high-FODMAP diet. The introduction of dietary interventions led to symptom remission. This report demonstrates how thorough anamnesis and careful physical examination are essential in elucidating the etiology of abdominal pain.